The Effect of Earnings Management and Financial Performance on Stock Returns Ahead of the Initial Public Offering with Company Size as Moderating Variable: Pengaruh Manajemen Laba dan Kinerja Keuangan terhadap Return Saham Menjelang Initial Public Offering dengan Ukuran Perusahaan sebagai Variabel Moderasi - Ratnasari, Dwi Ika; Widodo, Heri (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of earnings management and financial performance on stock returns, with firm size as a moderating variable (Study of Companies Listed on the Indonesia Stock Exchange in 2017-2020). The variables in this study use independent variables, dependent variables and moderating variables. The independent variables of the study are earnings management and financial performance. The dependent variable of the study is stock returns. The research moderating variable is firm size. This study uses a quantitative approach. The research sample was taken using a non-probability sampling method with purposive sampling technique, with a total sample of 166 companies. This study uses SEM (Structural Equation Model) analysis in testing the research hypothesis. strengthen the effect of financial performance on stock returns.